2021
DOI: 10.1111/geoj.12406
|View full text |Cite
|
Sign up to set email alerts
|

Using participatory video to share people’s experiences of neotropical urban green and blue spaces with decision‐makers

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To date, human experimentation has become more consistent with these media. Using full-color video as a proxy of real landscapes has been widely used in previous literature [29,30]. Research has demonstrated that natural exposure to videos provides emotional healing for those unable to access the outdoors, comparing it to real outdoor experiences, with both being emotionally beneficial and restorative [31]; Research has also shown that the healing effect of landscape color can be verified by creating a digital roaming landscape and inviting subjects to complete a Likert scale.…”
Section: Stimulimentioning
confidence: 99%
“…To date, human experimentation has become more consistent with these media. Using full-color video as a proxy of real landscapes has been widely used in previous literature [29,30]. Research has demonstrated that natural exposure to videos provides emotional healing for those unable to access the outdoors, comparing it to real outdoor experiences, with both being emotionally beneficial and restorative [31]; Research has also shown that the healing effect of landscape color can be verified by creating a digital roaming landscape and inviting subjects to complete a Likert scale.…”
Section: Stimulimentioning
confidence: 99%
“…Greenspace has been discussed concerning urban residents' social cohesion and perceived well-being. Researchers found that people regard greenspace as gathering places with family, friends or neighbors (Irvine et al, 2013;Schetke et al, 2016;Mao et al, 2020;Fisher et al, 2021;Sen and Guchhait, 2021) emphasizing that increasing social bond through the nearby natural environment prevents social isolation (Ward Thompson et al, 2016) and promotes environmental justice (Enssle and Kabisch, 2020). Especially for social minority groups, greenspace functions as a place for their unification and acculturation (leBrasseur, 2022).…”
Section: Greenspace Interactionsmentioning
confidence: 99%
“…The PV methodology is characterized by group or community co-creating videos on a topic, drawing collective perspectives according to what they feel is important and how they want it to be represented (Mistry and Berardi, 2012;Cai et al, 2019). PV combines the need to represent multiple viewpoints while capturing the complexities of the real world (Fisher et al, 2021). Through PV, local knowledge is integrated and influences the research process (Bignante et al, 2016;Milne, 2016), thus supporting dialogue between researchers and community members.…”
Section: Participatory Videomentioning
confidence: 99%
“…PV combines the need to represent multiple viewpoints while capturing the complexities of the real world (Fisher et al, 2021). It allows farmers to define what they feel is important in telling their story and how they want it to be represented.…”
Section: Participatory Videosmentioning
confidence: 99%